Inflammation and macrophage polarization are associated with Modic change type in lumbar radiculopathy - Wensen Li; Niek Djuric; Christiaan Mink; Carmen L.A. Vleggeert-Lankamp (Brain and Spine)
Introduction: Lumbar disc herniation (LDH) typically manifests as sciatica, attributed to nerve root mechanical compression and/or inflammation. Modic changes (MC), classified as type I or type II, are deemed to represent endplate vascular insufficiency and are hypothesized to create an inflammatory environment. Macrophages infiltrating disc tissue can be polarized into pro-inflammatory M1 or anti-inflammatory M2 phenotypes. Research question: This study aims to investigate the interplay among inflammatory cells, including M1 and M2 macrophages, Modic Changes, and hernia size and type in patients suffering from sciatica due to a LDH. Material and methods: This prospective cohort study selected patients undergoing microdiscectomy for LDH. Macrophage infiltration (CD68, CD192, CD163), MC classification on MRI, and hernia parameters were analyzed. Results: 132 out of 187 patients demonstrated macrophages in the lumbar disc tissue. Most samples demonstrated severe inflammation (50 %), and most macrophages were of the M1 phenotype (48 %). MC were present in 45 % of patients, and only 19 % of these demonstrated MC type I. MC type I were highly associated with both severe (p = 0.016) and M1 macrophage-dominant inflammation (p = 0.048). Larger and non-contained herniations associated with increased inflammation (p = 0.029/p = 0.002), while larger herniations associated with the presence of MC type II (p = 0.027). Discussion and conclusions: This study elucidates a close association of MC type I and M1 macrophage. MC type II were observed more often in patients with larger HNPs. This is indicative for MC typing as an important factor in prediction modelling and it suggests the potential for personalized treatment strategies.